The Influence of Environmental, Social, Governance, and Corporates Scandals on the Stock Volatility - Muhammad Brilian Wahyudyatmika; Christina Dwi Astuti (PT Mattawang Mediatama Solution, 2024)
The volatility of stocks is influenced by various factors, both internal andexternal to the company. This research aims to determine whether there is a relationship between Environmental, Social, Governance (ESG) performance and corporate controversies on stock volatility. The sample used in this study consists of companies listed on the Indonesia Stock Exchange for the period 2018—2022 and have an ESG rating from The London Stock Exchange Group (LSEG). Based on the analysis conducted, it is concluded that environmental performance negatively affects stock volatility, while social performance, governance performance, and corporate controversies do not have an impact on stock volatility.